A study of perceived ICT learning environments in Malaysian secondary schools - Wong, Su Luan; Lo, Yoon Mee; Bakar, Ab Rahim; Dietrich, Albert (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
This study seeks to investigate the extent to which the teaching and learning practices of a discrete Information and Communication Technology (ICT) subject are in accordance with the constructivist nature of ICT as perceived by Malaysian secondary school students. A survey methodology was employed such that modified items from the Constructivist Learning Environment Survey (CLES) questionnaire were adopted. It comprised five components of constructivist learning: Personal Relevance, Uncertainty of ICT, Shared Control, Critical Voice and Student Negotiation. Data were gathered from 440 participants. Findings from the present study indicate that three out of five components are sufficiently present in the ICT learning environment (Personal Relevance, Uncertainty of ICT and Student Negotiation). The other two components (Shared Control and Critical Voice), however, were not encouragingly present despite the positive intentions of the ICT curriculum.